Fuzzy hybrid multi-criteria decision making model for municipal solid waste disposal selection - Zamali Hj. Tarmudi (Fakulti Sains dan Teknologi, 2012)
In recent years, the tremendous increase of municipal solid waste generation in Malaysia has received significant attention from both the government and public communities. The increased amount cannot be totally absorbed by existing disposal sites.